2019
DOI: 10.1108/jedt-09-2018-0165
|View full text |Cite
|
Sign up to set email alerts
|

Engineering manipulation at nanoscale: further functional specifications

Abstract: Purpose Novel nanomaterials and nano-devices require further functional aspects that can be designed and supported using new nanomanipulation techniques allowing specific functions at the design phase. The nano-manipulator becomes a key instrument for technology bridging sub-nano to mesoscale. The integration of various operations in nano-devices requires sub-nanometer precision and highly stable manipulator. This paper aims to review various design concepts of recent nanomanipulators, their motion characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…reflector optical inspection. The review of the past nanomanipulators in patents [2] and published papers [3], [4] has revealed several types; standalone manipulators in different sizes e.g. large XY compliant [5], small manipulators housed inside transition electron microscopy (TEM) benefiting from its high-resolution imaging and analytic capability [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reflector optical inspection. The review of the past nanomanipulators in patents [2] and published papers [3], [4] has revealed several types; standalone manipulators in different sizes e.g. large XY compliant [5], small manipulators housed inside transition electron microscopy (TEM) benefiting from its high-resolution imaging and analytic capability [6].…”
Section: Introductionmentioning
confidence: 99%
“…grippers, sprayers, nano-tweezers. The existing quantified capabilities in terms of degrees of freedom, precision of motion, associated operations needed by the applications, and technology limitations of performances were reviewed in [3], [4]. Comparison has been made based on criteria such as degrees of freedom, sub-micrometer resolution with positioning precision per axis, available controlled operations for manipulation and whether these are operated in open or closed environment.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, развитие микротехники и нанотехники привело к необходимости в исследовании сил адгезии, как причины взаимного прилипания отдельных элементов микроэлектромеханических систем, нарушающих их работу [11]. Фактор прилипания, обусловленный силами адгезии, должен также учитываться в технике при использовании микро-и наноманипуляторов [12,13]. Адгезию можно изучать как один из механизмов трения качения.…”
unclassified